👤
a fost răspuns

Ex1 : 1/6+1/6 • 3

Ex2: 3x + 2 = 8


Răspuns :

                      ex 1                                                                                                                 1\6+1\6 *3 =                                                                                                                 1) 1\6*3 =1\6*1\3=3\6 apoi simplifica la 3 si primesti 1\2                                             2) 1\6+1\2 = aduci la un numitor comun 1\6+3\6 =4\6 apoi sim[plifici la 2 si primesti 2\3                                                                                                                                            ex 2                                                                                                       3x+2=8                                                                                                                    3x=8-2                                                                                                                     3x=4                                                                                                                        x=4 impartit la 3                                                                                                         x=1.3
ex1: 1/6+1/6*3=1/6+3/6=4/6=2/3
ex2: 3x+2=8;3x=8-2;3x=6;x=6/3;x=2